Land Relations in the Context of Social and Economic Transformations of the Ukrainian Countryside During the Years of Independence: Scientific Assessments and Forecasts - Коріненко, Павло; Падалка, Сергій; Váradi, Natália (Український історичний журнал, 2021)
The purpose of the study is to analyze the transformations of land relations in the Ukrainian countryside with gaining independence. Changes in land use, land management, as well as the emergence of new organizational and economic forms of management in the agrarian sector were radical, and therefore ambiguous in their nature. General scientific methods were used in the study, in particular comparativehistorical and systemic-structural, which helped to organize a significant number of source material, reproduce and compare the direction of land relations transformation at different stages of this process. The problem-chronological approach was used to determine the structure of the study. The scientific novelty consists in researching the problem, which has not been investigated in Ukrainian historiography in such a formulation and chronological framework. Agrarian reform in Ukraine, first of all, the reform of land relations, has been consistently considered from lease spreading, land subdividing among the peasants to the opening of the agricultural lands market. Objective and subjective factors, which complicated these processes and, in particular, lagging behind in the formation of a complex of legal bases were analyzed. Conclusions. The influence of land relations transformation on achievements and losses in the Ukraine’s agrarian sector were highlighted. The authors state that the hasty introducing new agrarian forms of land management without proper theoretical justification, financial support has made the reform process poorly predictable for 30 years. For a long time, peasants were unsure of the irreversibility of land relations transformation, which is confirmed by the rather slow rate of State certificates of land shares ownership. It has been mentioned that the authorities were aware of the problem complexity, so a slow transition from collective and state farm system – through CAEs (collective agricultural enterprises) – to PPFs (personal peasant farms) and PSF (personal subsidiary farms) was proposed. Agro-firms and agro-holdings were the culmination of a new structure of land management. The changes in the structure of crops and livestock farming, which became the result of land relations transformation, were analyzed. Changes in the lives of peasants were traced, first of all, the attitude of most of them to small-scale production. A step-by-step review of the condition of the agrarian sector material and technical basis was made.